Osteoporotic fractures: an unrecognized adverse event of immune checkpoint inhibitors? - Carrie Ye; Manar Elsayed (Journal for ImmunoTherapy of Cancer)
The widespread use of immune checkpoint inhibitors (ICIs) in clinical practice has broadened our understanding of their immune-related adverse events (irAEs). IrAEs, including musculoskeletal adverse events, remain a significant concern. While ICI-associated arthritis is a well-documented musculoskeletal side effect of ICI therapy, the direct effects of ICIs on bone in patients with cancer are poorly understood. There is emerging evidence to support the hypothesis that ICIs adversely impact bone turnover and can lead to osteoporosis and fragility fractures, which are not currently recognized as irAEs.